2011
DOI: 10.1158/1541-7786.mcr-10-0394
|View full text |Cite|
|
Sign up to set email alerts
|

S100A8/A9 Activate Key Genes and Pathways in Colon Tumor Progression

Abstract: The tumor microenvironment plays an important role in modulating tumor progression. Earlier, we showed that S100A8/A9 proteins secreted by myeloid-derived suppressor cells (MDSC) present within tumors and metastatic sites promote an autocrine pathway for accumulation of MDSC. In a mouse model of colitis-associated colon cancer, we also showed that S100A8/A9-positive cells accumulate in all regions of dysplasia and adenoma. Here we present evidence that S100A8/A9 interact with RAGE and carboxylated glycans on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
296
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 300 publications
(315 citation statements)
references
References 80 publications
(116 reference statements)
14
296
2
3
Order By: Relevance
“…These data indicate that p38 MAPK mediates the NF-κB activation induced by S100A8/A9. These results are consistent with reports that S100A8/A9 promotes activation of MAP kinase and NF-κB signaling pathway in breast cancer, leukemia, neuroblastoma, prostate cancer and colon cancer cells (Ghavami et al, 2008b;Hermani et al, 2006;Ichikawa et al, 2011). In addition, we found that activation of p38 MAPK and NF-κB was associated with the S100A8/ A9-induced cell migration and invasion as evidenced by attenuation of the migration and invasion by the SB203580 and Bay (Fig.…”
Section: A B Csupporting
confidence: 93%
See 4 more Smart Citations
“…These data indicate that p38 MAPK mediates the NF-κB activation induced by S100A8/A9. These results are consistent with reports that S100A8/A9 promotes activation of MAP kinase and NF-κB signaling pathway in breast cancer, leukemia, neuroblastoma, prostate cancer and colon cancer cells (Ghavami et al, 2008b;Hermani et al, 2006;Ichikawa et al, 2011). In addition, we found that activation of p38 MAPK and NF-κB was associated with the S100A8/ A9-induced cell migration and invasion as evidenced by attenuation of the migration and invasion by the SB203580 and Bay (Fig.…”
Section: A B Csupporting
confidence: 93%
“…This is consistent with the finding that S100A8/A9 provoked p38 MAPK while JNK phosphorylation was unaffected in human prostate and breast cancer cells (Ghavami et al, 2008b;Hermani et al, 2006). In contrast, S100A8/A9 activates ERK and JNK but not p38 MAPK in colon cancer cells (Ichikawa et al, 2011). Therefore, the effect of S100A8/A9 on MAPK signaling may depend on the cancer cell types.…”
Section: A B Csupporting
confidence: 90%
See 3 more Smart Citations